2022
DOI: 10.1021/acscatal.2c04238
|View full text |Cite
|
Sign up to set email alerts
|

Operando Identification of Dynamic Photoexcited Oxygen Vacancies as True Catalytic Active Sites

Abstract: The complex structural evolution of catalysts under realistic reaction conditions causes great difficulty in identifying true active sites and further understanding the correlations between the dynamic behavior and the catalytic property. Herein, we developed a set of operando electron paramagnetic resonance (EPR) measurements to investigate the dynamic behavior of true active sites, particularly the atomic surface structures and interfacial processes under reaction conditions. By constructing reduced TiO2 as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 77 publications
0
11
0
Order By: Relevance
“…At the same time, the peak area ratio corresponding to Fe 2+ enlarged with the reduction temperature (≤200 °C), which implies that more Fe 3+ species are reduced to Fe 2+ species, forming more oxygen vacancy defects (i.e., O v –Fe 2+ sites) . In addition, in situ EPR characterization was used to further probe the effect of reduction temperature on the O v defects, as shown in Figure d. , The signals at a g -factor of 2.003 were attributed to the surface Fe 2+ defect and O v . The increase of the O v signal with reduction temperature depicted that O v –Fe 2+ defect sites were directly related to the Pt δ− species.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, the peak area ratio corresponding to Fe 2+ enlarged with the reduction temperature (≤200 °C), which implies that more Fe 3+ species are reduced to Fe 2+ species, forming more oxygen vacancy defects (i.e., O v –Fe 2+ sites) . In addition, in situ EPR characterization was used to further probe the effect of reduction temperature on the O v defects, as shown in Figure d. , The signals at a g -factor of 2.003 were attributed to the surface Fe 2+ defect and O v . The increase of the O v signal with reduction temperature depicted that O v –Fe 2+ defect sites were directly related to the Pt δ− species.…”
Section: Resultsmentioning
confidence: 99%
“…25 In addition, in situ EPR characterization was used to further probe the effect of reduction temperature on the O v defects, as shown in Figure 3d. 26,27 The signals at a g-factor of 2.003 were attributed to the surface Fe 2+ defect and O v . The increase of the O v signal with reduction temperature depicted that O v −Fe 2+ defect sites were directly related to the Pt δ− species.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that as the reaction proceeded, there was a noticeable increase in activity. This is likely due to in situ V O generation under UV irradiation …”
Section: Resultsmentioning
confidence: 99%
“…This is likely due to in situ V O generation under UV irradiation. 66 Since catalyst activity has been correlated to surface V O content, we further investigated BOHP oxygen occupancy via EDS analysis (Table S6). The results show that the ratio of oxygen to bismuth (O:Bi) and oxygen to phosphate (O:P) decreased as the NH 4 OH volume increased, suggesting increased V O concentrations near the particle surfaces.…”
Section: +mentioning
confidence: 99%
“…Moreover, another reason for the gradual decrease in ECSA values could be the S filling O v behavior, due to O v being considered to be the active site in the electrochemical process. 60,69 Interestingly, the ECSA value of NiFe-LDHS was not the largest, indirectly suggesting that the intrinsic activity of electrochemical sites played a dominant role in electrochemical performance. Thus, it can be concluded that the synergistic effect of O v and S was mainly reflected by the intrinsic activity of electroactive materials, which essentially determined the electrochemical performance.…”
Section: Mechanism Investigationmentioning
confidence: 99%